Association of four metalloids in the serum and urine of individuals with major depressive disorders: a case–control study - He, Lei; Li, Shilong; Huang, Yan; Zhu, Yuxing; Fan, Lingzi; Zhang, Hongwei; Hou, Xiaofang; Li, Xiaoxin; Deng, Hongxin; Guo, Xueli; Liu, Chunxiao; Hu, Chen; et al. (Frontiers in Psychiatry, 2024)
Major depressive disorder (MDD) pathogenesis may involve metalloids in a significant way. The aim of our study was to identify potential links between between MDD and the metalloid elements [boron (B), germanium (Ge), arsenic (As), antimony (Sb)]. Totally, 72 MDD cases and 75 healthy controls (HCs) were recruited from Zhumadian Second People's Hospital in Henan Province, China. Levels of four metallic elements (B, Ge, As, and Sb) in serum and urine were measured using inductively coupled plasma mass spectrometry (ICP-MS). In comparison to the HCs, the B, As, and Sb levels were considerably lower in the MDD group (p<0.05) in the serum; the MDD group had significantly higher (p<0.05) and significantly lower (p<0.001) B and Sb levels in urine. After adjusting for the potential confounders, serum B (OR=0.120, 95%C1, 0.048, 0.300, p<0.001) and Sb (OR=0.133, 95%C1, 0.055, 0.322, p<0.001) showed a negative correlation with MDD. Urine B had a negative correlation (OR=0.393, 95%C1, 0.193, 0.801, p=0.01) with MDD, while urine Sb had a positive correlation (OR=3.335, 95%C1, 1.654, 6.726, p=0.001) with MDD. Our current research offers insightful hints for future investigation into the function of metalloids in connection to MDD processes.